Maximum gas production rate for salt cavern gas storages. (1st November 2021) - Liu, Xin; Shi, Xilin; Li, Yinping; Li, Peng; Zhao, Kai; Ma, Hongling; Yang, Chunhe
Abstract: The maximum gas production rate from salt cavern gas storages is a key parameter affecting its operating safety and peak-shaving performance. However, there is no mature and reliable method for design in it. In this study, the components of a salt cavern gas storage were separated, and many factors affecting the gas production rate are studied in terms of the safety of cavern, tubing and wellhead. These include mechanical stability and volume shrinkage of the cavern, erosion and corrosion of the tubing, generation of hydrate and condensate at the wellhead. Methods are provided for determining the gas production rate to avoid adverse effects, and the thermodynamic parameters during production are modeled mathematically and solved. Finally, an evaluation system for selecting maximum gas production rate from a salt cavern gas storage is proposed and has been compiled into software UGS-GP-design. Applying it to Jintan T5-2 salt cavern gas storage, the feasibility of the proposed method was verified. The study is mostly applicable to natural gas storage, as well as offering theoretical basis and methodological support for salt cavern air and hydrogen storage. Highlights: Operation safety and peak-shaving performance varies with gas production rates. Selecting gas production rates in terms of safety in cavern, tubing and wellhead. Thermodynamic parameters during production are modeled mathematically and solved. Proposed method to design maximum gas production rate and compiled into software. Verified design method using case application and field data.